Pemikiran Ibn Khaldun Mengenai Ilmu dan Sosio-Budaya - Hj Ab Majid, Mohamad Kamil (Jurnal Usuluddin, 1997)
The study is an attempt to analyse the point of view of Ibn Khaldun, a great muslim thinkers upon llm and Social-life. In the discussion, an attempt is also made to alobrate his views of country planning and economy value.